2013
DOI: 10.1525/cond.2013.110202
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the Connecticut Warbler Increases with Size of Patches of Coniferous Forest

Abstract: The Connecticut Warbler {Oporornis agilis) is a rare and declining neotropical migrant that breeds in the north-central United States and south-central Canada. To better understand the species' habitat needs, we analyzed 371 observations of the Connecticut Warbler over 18 years at 86 sites in 28 stands of forest in northern Minnesota. We considered the habitat and landscape at three spatial scales (buffer radii of 100, 500, and 1000 m) and regressed combinations of habitat variables with two response variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…GAP level 4 data were reclassified into 18 land cover types hypothesized to affect bird species breeding in lowland coniferous habitats (Table 1). A variety of metrics of landscape pattern similar to those used in previous modeling efforts for these species were derived from the reclassified GAP data (Hawrot and Niemi 1996, Drolet et al 1999, Crozier and Niemi 2003, Lapin et al 2013), but many were highly correlated and only patch richness and number of patches were retained for analysis. Individual patches were defined as contiguous (eight grid cell, nearest neighbor) units of GAP level 4 land cover data.…”
Section: Environmental Predictor Datamentioning
confidence: 99%
See 4 more Smart Citations
“…GAP level 4 data were reclassified into 18 land cover types hypothesized to affect bird species breeding in lowland coniferous habitats (Table 1). A variety of metrics of landscape pattern similar to those used in previous modeling efforts for these species were derived from the reclassified GAP data (Hawrot and Niemi 1996, Drolet et al 1999, Crozier and Niemi 2003, Lapin et al 2013), but many were highly correlated and only patch richness and number of patches were retained for analysis. Individual patches were defined as contiguous (eight grid cell, nearest neighbor) units of GAP level 4 land cover data.…”
Section: Environmental Predictor Datamentioning
confidence: 99%
“…Despite this, only one study has completed a detailed analysis of Connecticut Warbler breeding habitat in Minnesota. In the Superior and Chippewa National forests, Lapin et al (2013) found the Connecticut Warbler primarily in large contiguous patches of lowland conifer forests often surrounded by upland coniferous forest, as opposed to upland deciduous forest. Models with local stand variables (100 m buffer), including detailed measurements of forest stand characteristics such as tree and shrub density, performed poorly.…”
Section: Individual Speciesmentioning
confidence: 99%
See 3 more Smart Citations